To beat, or not to beat, that is question! The spectrum of ciliopathies. Issue 8 (25th June 2018) - Kempeneers, Céline; Chilvers, Mark A.
Abstract: Cilia are widely distributed throughout the human body, and have numerous roles in physiology, development, and disease. Ciliary ultrastructure is complex, consisting of nine parallel microtubules doublets, with or without motor dynein arms and a central pair of microtubules. Classification of cilia has evolved over time, and currently, four main classes are described: motile and non‐motile cilia with a "9 + 2" structure, and motile and non‐motile cilia with a "9 + 0" structure, which depend on the presence or absence of dynein arms and a central pair. Ciliopathies are inherited multisystem disorders of cilia, and may present with a varied spectrum of genotypes and phenotypes. Motor and sensory ciliopathies were historically considered as distinct dysfunctions of motile and non‐motile cilia, but recent data indicate that the classical features of motor and sensory cilia may overlap.